“If there was one piece of advice I could give you as you go on placement it would be about ‘soft skills’”: Practice Teacher’s advice to Social Work students - Flanagan, Niamh; Wilson, Elaine (The Journal of Practice Teaching and Learning, 2025)
Practice teachers are the fulcrum of social work practice education: the point around which practice placement revolves and the principal point of support for students on placement. Given their experience, practice teachers are best placed to advise students about going on placement. This research sought to garner the principal advice that Irish social work practice teachers would offer to students as they set out on their placement. Contrary to expectation, the practice teachers largely chose to focus their advice on the, somewhat neglected area of soft skills, elevating this to similar status as the ‘hard skills’ of practice. Preliminary research findings from this research were shared in a social-media-friendly spoken-word-video in order to rapidly disseminate the advice to students (Flanagan & Wilson, 2023a) and this article further interrogates the advice, placing it in the context of academic literature on soft skills and their contribution to the development of a ‘professional self’. The article maps the key soft skills essential to placement and practice according to literature and operationalises these skills in the advice of practice teachers.